ATCA study of Small Magellanic Cloud supernova remnant 1E 0102.2–7219 - Alsaberi, Rami Z.E.; Filipović, M. D.; Dai, S.; Sano, H.; Kothes, R.; Payne, J. L.; Bozzetto, L. M.; Brose, R.; Collischon, Caroline; Crawford, E. J.; Haberl, F.; Hill, T.; et al. (Monthly Notices of the Royal Astronomical Society, 2024)
We present new and archival Australia Telescope Compact Array and Atacama Large Millimeter/submillimeter Array data of the Small Magellanic Cloud supernova remnant 1E 0102.2–7219 at 2100, 5500, 9000, and 108 000 MHz; as well as H I data provided by the Australian Square Kilometre Array Pathfinder. The remnant shows a ring-like morphology with a mean radius of 6.2 pc. The 5500 MHz image reveals a bridge-like structure, seen for the first time in a radio image. This structure is also visible in both optical and X-ray images. In the 9000 MHz image, we detect a central feature that has a flux density of 4.3 mJy but rule out a pulsar wind nebula origin, due to the lack of significant polarization towards the central feature with an upper limit of 4 per cent. The mean fractional polarization for 1E 0102.2–7219 is 7 ± 1 and 12 ± 2 per cent for 5500 and 9000 MHz, respectively. The spectral index for the entire remnant is −0.61 ± 0.01. We estimate the line-of-sight magnetic field strength in the direction of 1E 0102.2–7219 of ∼44 μG with an equipartition field of 65 ± 5 μG. This latter model uses the minimum energy of the sum of the magnetic field and cosmic ray electrons only. We detect an H I cloud towards this remnant at the velocity range of ∼160–180 km s−1 and a cavity-like structure at the velocity of 163.7–167.6 km s−1. We do not detect CO emission towards 1E 0102.2–7219.
CRIS-Team Scopus Importer:2023-12-01
Keywords: ISM: individual objects; ISM: magnatic fields; ISM: supernova remnants; Radio continuum: ISM